2018
DOI: 10.4236/ojn.2018.811060
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs and Experiences of Fear of Hypoglycemia and Use of Uncooked Cornstarch before Bedtime in Persons with Type 1-Diabetes

Abstract: Introduction: Among persons living with type 1-diabetes hypoglycemia and fear of hypoglycemia remain limiting barriers for achieving optimal glucose control and a good quality of life. Fear of hypoglycemia has been found stable over time if not treated. Uncooked cornstarch has been found to reduce the risk of hypoglycemia but has not been studied in relation to fear of hypoglycemia. The aims of this study were to through clinical data, self-reported measures and clinical interviews explore subjects' experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…There have been a number of single case studies that have found cognitive behavioural therapy (CBT) to be an effective treatment for FOH 9–11 . A randomised control trial produced similar findings 12 . However, none of these studies took place within primary care psychological therapy services.…”
Section: Introductionmentioning
confidence: 99%
“…There have been a number of single case studies that have found cognitive behavioural therapy (CBT) to be an effective treatment for FOH 9–11 . A randomised control trial produced similar findings 12 . However, none of these studies took place within primary care psychological therapy services.…”
Section: Introductionmentioning
confidence: 99%